2022
DOI: 10.3390/plants11202672
|View full text |Cite
|
Sign up to set email alerts
|

Phyto-Friendly Soil Bacteria and Fungi Provide Beneficial Outcomes in the Host Plant by Differently Modulating Its Responses through (In)Direct Mechanisms

Abstract: Sustainable agricultural systems based on the application of phyto-friendly bacteria and fungi are increasingly needed to preserve soil fertility and microbial biodiversity, as well as to reduce the use of chemical fertilizers and pesticides. Although there is considerable attention on the potential applications of microbial consortia as biofertilizers and biocontrol agents for crop management, knowledge on the molecular responses modulated in host plants because of these beneficial associations is still incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 165 publications
0
8
0
Order By: Relevance
“…Several studies have reported that PGPM can provide protection to plants against phytopathogens by inducing the plant's defense mechanisms, which are known as induced systemic resistance (ISR). This phenomenon has been discussed in detail in the review article 59 . As a result of ISR, the cell wall is strengthened by increased lignin production and callose apposition, which slows the spread of phytopathogens across plant tissues 60 .…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have reported that PGPM can provide protection to plants against phytopathogens by inducing the plant's defense mechanisms, which are known as induced systemic resistance (ISR). This phenomenon has been discussed in detail in the review article 59 . As a result of ISR, the cell wall is strengthened by increased lignin production and callose apposition, which slows the spread of phytopathogens across plant tissues 60 .…”
Section: Discussionmentioning
confidence: 91%
“…Rojas-Sánchez, et al [ 124 ] explained how PGPF dwells in root cells, root surfaces, and the outer layers of root cells. De Palma, et al [ 157 ] reported how Trichoderma spp. can be introduced into plant roots during the seedling stage of plant growth to ensure a beneficial relationship in improving plants’ health and preventing disease invasion.…”
Section: Pgpf As An Alternative To Chemical Derivatives In Crop Plant...mentioning
confidence: 99%
“…Phytostimulators are rhizosphere or endophyte microorganisms, fungi, and bacteria, which can influence plant growth and development by affecting plant hormone metabolism, either through the production of phytohormones such as auxins, cytokinins, and gibberellins or by interfering with plant endogenous hormone homeostasis [ 10 , 11 ]. This type of PGPM facilitates implantation, accelerates growth, and promotes greater plant vigor, but can also mitigate the damaging effects of abiotic stresses.…”
Section: Plant-beneficial Microbes and The Concept Of Probioticsmentioning
confidence: 99%